(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Safeguarding the eHealth information of patient’s stands utmost paramount for performing web-scale analytics and reporting applications. Apparently, there has been data breaches that have become quite prominent lately. The prime target is towards resolving the issue of determining robust and trustworthy analytics in a secured way that fulfills product pre-requisites. There is proposal of an improved version of eHealth data privacy preserving system apt for the cloud space. The proposed system yields in at par integration, interoperability, availability as well as sharing of healthcare information amidst various healthcare providers, patients, and practitioners. There is distribution of patient’s health details amidst the various Treatment Service Company which are combined and put away in the cloud space thus building the patient’s overall eHealth information. Cloud technology benefits by providing prompt Internet access as well as feasible access to eHealth information from any location and platform at any given time. There has been a significant rise in the volume of the healthcare information produced as well as the difficulty involved in its data type. To resolve this, technique of blockchain has been recommended for determining effective measures by the practitioners at the right time. Moreover, the proposed system imbibes certain important security constraints and access control mechanism that ensures security, integrity, and protection of Ehealth information via blockchain using SHA- 256. Above all, the said system encourages development of a system that is economical, highly efficient and secure.